Analisa Perbandingan Percepatan Penyelesaian Proyek Dengan Metode (Studi Kasus : Proyek Mercu Suar,Yogyakarta) - Jajang Atmaja - (Jurnal Ilmiah Poli Rekayasa, 2019)
Time constraints are often a problem in construction projects. Project scheduling and consistent evaluation are needed so that the project is completed on time. Evaluation is applied using performance intensity methods and Microsoft Project. Performance Intensity is a calculation carried out to determine the pace of project work. Performance intensity provides information on how quickly an activity can be completed. For the calculation of Performance Intensity use PPI, API and CPI. To control work in the field using CCS and CCP. Evaluation to find out the time performance applied to the Yogyakarta Lighthouse project. The project is planned to be completed on December 14, 2014 with a duration of 266 days. Evaluation is carried out for 35 periods. The results of this evaluation are differences in the analysis of the final day between the method of Performance Intensity and Microsoft project. The final day analysis of Performance Intensity at week 35 for 279 days, while analysis of Microsoft Project for 280 days. Differences in the range of predictions for the day-to-day analysis of a project are caused by the Performance Intensity method using the average cumulative work rate as a benchmark that changes every period. To pursue delays, the project acceleration method is used, namely Schedule. The time needed for the Schedule is 80 days.